Solar Landscapes. Aesthetics in the Energy Transition - Furia, Paolo (Aisthesis, 2025)
This essay explores the aesthetics of solar landscapes in the framework of a broader investigation about the concept of landscape and its semantic richness. The article consists of four paragraphs. In the first, the terms territory and landscape are introduced to properly distinguish between disputes over land use and landscape perception. The second paragraph reflects on energy landscapes as particular cases of cultural landscapes that are typical of modernity and are generally not associated with positive aesthetic values. After a brief examination of the aesthetic issues related to energy landscapes in general, the third paragraph deals specifically with solar landscapes and offers a philosophical commentary on part of today’s literature, which is mainly drawn from the fields of energy economics and landscape planning. Finally, in the fourth paragraph, I will show that energy and solar landscapes also deserve attention from an aesthetic point of view: Although they are unavoidable from a territorial point of view, they still need to be socially and aesthetically accepted to be fully realised as full-fledged landscapes.